2020
DOI: 10.23869/bphjbr.25.2.20202
|View full text |Cite
|
Sign up to set email alerts
|

Combination of culture and dyeing conditions on cloth color dyed with mixed fungi dyes

Abstract: This study aimed to examine the dyes production of mixed Aspergillus and Paecilomyces on different culture conditions and evaluate the combination between culture and dyeing conditions on cloth color by the fungal dyes. The different media consist of mineral salt glucose (MSG) medium and mineral salt sucrose (MSS) medium were evaluated. Additionally, different culture conditions such as C and N sources, incubation temperature, and pH of the media were evaluated together with variation of dyeing conditions incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The control's painted cotton cloth color (only the fungal dyes) was 65B redpurple (Table 6 and Figure 3). Similar results were reported by Suciatmih et al (2018), Suciatmih (2019) and Suciatmih (2020) that the same mixed fungi produced the same color pigment that can be used to dye cloth. The dye is included in the substantive dyes group because the dye can directly paint textile fibers or give good color when used alone (Marie et al 2015).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The control's painted cotton cloth color (only the fungal dyes) was 65B redpurple (Table 6 and Figure 3). Similar results were reported by Suciatmih et al (2018), Suciatmih (2019) and Suciatmih (2020) that the same mixed fungi produced the same color pigment that can be used to dye cloth. The dye is included in the substantive dyes group because the dye can directly paint textile fibers or give good color when used alone (Marie et al 2015).…”
Section: Resultssupporting
confidence: 87%
“…However, the resulting colors were different from the control colors (65B red-purple). Our previous study (Suciatmih & Yuliar 2018;Suciatmih 2020) reported that changing the dye pH can change the dye color of mixed Aspergillus and Paecilomyces. The dyes' ionic nature enabled the changes of the molecule structures according to the prevailing pH values and results in different colors and hues at different pH values (Mishra et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations